Analisis Kinerja Keuangan Perusahaan Badan Usaha Milik Negara Sebelum dan Sesudah Privatisasi di Indonesia - Kirmizi Kirmizi (Universitas Riau, 2009)
This study examines the financial performance of State-Owned Enterprises before andafter privatization. The population of the research is State-Owened Enterprises which are priva-tized through Initial Public Offering (IPO). The sample drawn using the method of purposivesampling with its criteria are listed at least three years in Indonesia Stock Exchange and theyissued at least three years data of financial statement on before and after privatization. Based onthe sampling criteria, this research was addressed to nine State-Owened Enterprises. Researchdata is collected from the yearly financial reporting for three years after IPO. To evaluate theperformance of enterprise, researcher required some indicators to analyse data such as profit-ability ratio, assets productivity ratio, leverage ratio, and payout ratio. The statistic instrumentused in this study is Wilcoxon’s Signed Rank Test. The result of the research was indicated that theperformance of State-Owened Enterprises during three years before privatization tend to in-crease, although, few of them on the sample show tend to decrease based on the indicators used.Based on the analysis of indicators used, return on investment of PT.Telkom, PT.Timah, andPT.Aneka Tambang is incerase, but the others were vise versa. There are also three enterprisesincerasing in return on equity, but six of them are decrease. However, five of nine state-owenedenterprises could increase their return on sale and dividen payout, while assets turnover, totaldebt to assets, and dividen to sale have no significant influence on the increasing of financialperformance in state-owned enterprises. The conclusion of this research found that three indica-tors of asset turnover, total debt to assets, and devidend to sale showed that privatization programeof State-Owened Enterprises has no effect on financial performance.